(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Effective management of retinal diseases, especially diabetic retinopathy, is crucial for preventing severe visual complications. Collaboration between ophthalmologists and endocrinologists plays a fundamental role in the effective treatment of this condition, aiming to preserve vision and improve patients’ quality of life. Methods: A bibliographic review was conducted to understand the management of retinal diseases and the therapeutic association between ophthalmology and endocrinology in the treatment of diabetic retinopathy. We used databases such as MEDLINE, PubMed, and Scielo to identify relevant articles published in the last 20 years. Inclusion and exclusion criteria were defined to ensure the selection of pertinent studies. Results: After the search and selection of articles, patterns and trends in the management of diabetic retinopathy were identified. A variety of treatment options were located, including laser photocoagulation, intravitreal injections of medications, and vitreoretinal surgery. The importance of metabolic control of diabetes to prevent retinal damage was noted. The analysis of the studies also highlighted that the interaction between these specialties ensures better clinical outcomes. Conclusion: The importance of collaboration between ophthalmologists and endocrinologists in the management of diabetic retinopathy is reinforced. An integrated approach that considers both ophthalmological and endocrinological aspects of the disease is essential to provide effective care to patients. This cooperation can result in better visual outcomes and quality of life for those affected by diabetic retinopathy.